THE INFLUENCE OF MEDIA ON PERCEPTION OF BODY IMAGE IN MEDICAL STUDENTS OF PESHAWAR, PAKISTAN - Ali, Muhammad; Sethi, Mifra Rauf; Irfan, Muhammad (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the effect of media influence on perception of body image and eating attitude in students of medical and dental institutes of Peshawar-Pakistan. Methodology: A cross-sectional survey was conducted at medical and dental institutes of Peshawar, Pakistan from January to March 2019. All students from 1st year to final year were invited to complete Body Image States Scale (BISS), Eating Attitude Test (EAT-26) and Socio-cultural Attitudes Towards Appearance Questionnaire (SATAQ-3), along with providing demographic data on a semi structured proforma. The data was analyzed using SPSS-25, with Chi-square test and Pearson correlation test used as tests of significance. Results: The mean age of the sample (n=908) was 20.84+1.7 years. There were 529 (58.3%) females, most of the sample was collected from Private sector (n=841, 92.6%) and from first year (n=289, 31.8%). The Cronbach’s Alpha Reliability of BISS in our study was 0.866, 0.834 for EAT-26 and 0.888 for SATAQ-3. According to the responses, there were 430 (47.4%) students having issues of body image, 387 (42.6%) had problems with eating attitude and 502 (53.3%) students were more influenced by the media. The Pearson correlation showed that body image, media influence and eating attitude are significantly positive correlated with one another at p value of <0.01. Conclusion: There is influence of media both on body image and eating attitude. The results of cronbach’s alpha reliability of all the scales used in this study suggest that these scales can reliably be used in our setup.